2007
DOI: 10.1159/000108108
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Mineral Content in Type-2 Diabetic Patients and Their Association with the Metabolic Syndrome

Abstract: Background: Metabolic syndrome is a clinical disorder that is becoming more prevalent in Spain. The syndrome encompasses a set of metabolic disorders such as type-2 diabetes mellitus, hypertension, dyslipidemia, and obesity, which may be associated with variations in serum levels and poor delivery of certain mineral elements. Methods: This study attempted to ascertain whether metabolic syndrome might be linked to alterations in serum levels of the mineral elements magnesium, copper, zinc, chromium, and nickel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 43 publications
4
52
1
3
Order By: Relevance
“…In the present study, the correlation of essential and nonessential elements in scalp hair of DM-2 patients of both genders related to non-diabetic subjects belonging to Pakistan and Ireland was carried out. The results presented in Table 4 for healthy subjects and DM-2 patients confirm higher levels of Cd and Pb while lower values of Mg, Mn, Zn and Cr are associated with diabetes, which are consistent with other studies [31][32][33][34]. The results showed that the level of Mg was significantly lower in scalp hair samples of DM-2 patients as related to referents (P <0.001 ).…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, the correlation of essential and nonessential elements in scalp hair of DM-2 patients of both genders related to non-diabetic subjects belonging to Pakistan and Ireland was carried out. The results presented in Table 4 for healthy subjects and DM-2 patients confirm higher levels of Cd and Pb while lower values of Mg, Mn, Zn and Cr are associated with diabetes, which are consistent with other studies [31][32][33][34]. The results showed that the level of Mg was significantly lower in scalp hair samples of DM-2 patients as related to referents (P <0.001 ).…”
Section: Discussionsupporting
confidence: 89%
“…At the same time, zinc is a critical component of the catalytic site of .300 enzymes, implicated in synthesis, storage, and secretion of insulin, as well as being a signaling molecule after insulin secretion (5). Some studies have investigated possible associations between zinc status and diabetes; most reported that patients with diabetes had lower serum/plasma zinc levels (6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Interactions Between Zinc Transporter-8 Gene (Slc30a8) and Pmentioning
confidence: 99%
“…Transition metal ions strongly bind to phospholipids and alter the liposome bilayer and increase their susceptibility to lipid peroxidation (Oteiza et al 2004). Both the essentiality and toxicity of these metals ions in the pathogenesis of diabetes mellitus and diabetic complications are often reported (Walter et al 1991;Aguilar et al 2007;Zheng et al 2008). Transition metals ions also play a role in protein glycation induced by hyperglycemia.…”
mentioning
confidence: 99%